2016
DOI: 10.1016/j.ejcb.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Loss of endothelial barrier integrity in mice with conditional ablation of podocalyxin (Podxl) in endothelial cells

Abstract: Podocalyxin (Podxl) has an essential role in the development and function of the kidney glomerular filtration barrier. It is also expressed by vascular endothelia but perinatal lethality of podxl(-/-) mice has precluded understanding of its function in adult vascular endothelial cells (ECs). In this work, we show that conditional knockout mice with deletion of Podxl restricted to the vascular endothelium grow normally but most die spontaneously around three months of age. Histological analysis showed a nonspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…To reduce the magnification and increase the visible area while still viewing individual RNAs, we applied 4-rounds of clampFISH to mouse kidney samples and probed for PODXL mRNA, an gene that is highly expressed in podocytes 18 , and observed specific expression of clampFISH signal in the appropriate regions (Figure 2b, Supplementary Figure 4). Interestingly, clampFISH further revealed that PODXL also expressed in the kidney endothelium, a signal that was only faintly visible by single molecule RNA FISH, but was clearly detected by clampFISH at low magnification ( Figure 2b) consistent with previous findings that PODXL is expressed at low levels in the kidney endothelium 19 .…”
supporting
confidence: 77%
“…To reduce the magnification and increase the visible area while still viewing individual RNAs, we applied 4-rounds of clampFISH to mouse kidney samples and probed for PODXL mRNA, an gene that is highly expressed in podocytes 18 , and observed specific expression of clampFISH signal in the appropriate regions (Figure 2b, Supplementary Figure 4). Interestingly, clampFISH further revealed that PODXL also expressed in the kidney endothelium, a signal that was only faintly visible by single molecule RNA FISH, but was clearly detected by clampFISH at low magnification ( Figure 2b) consistent with previous findings that PODXL is expressed at low levels in the kidney endothelium 19 .…”
supporting
confidence: 77%
“…Intriguingly, although Podxl loss cripples the ability of endothelial cells to form appropriate intact monolayers in vitro, we observed no overt severe vascular defects due to Podxl loss in vivo at steady state. Podxl-deficient mice exhibited only a modest delay in the opening of vascular lumens during embryogenesis and a modest increase in permeability in adulthood (17,44,45). Thus, in vivo there appear to be sufficiently redundant mechanisms to ensure appropriate formation of properly patent vessels to allow survival in the absence of Podxl.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA via ROCK2b was found to prevent vascular leakage during leucocyte diapedesis and S1P was proposed to enhance barrier function at least in part via RhoA and ROCK . On the other hand, endothelial cells deficient in podocalyxin have delayed barrier recovery and sustained RhoA activation indicating a negative effect of RhoA . Moreover, it was shown by FRET sensors that Rac1 reduces tension applied on AJs, whereas ROCK had the opposite effect indicating that Rac1 but not RhoA stabilizes AJs …”
Section: Maintenance and Stabilization Of The Endothelial Barrier In mentioning
confidence: 99%
“…163,169,170 On the other hand, endothelial cells deficient in podocalyxin have delayed barrier recovery and sustained RhoA activation indicating a negative effect of RhoA. 171 Moreover, it was shown by FRET sensors that Rac1 reduces tension applied on AJs, whereas ROCK had the opposite effect indicating that Rac1 but not RhoA stabilizes AJs. 154 The structural basis for RhoA regulation at cell junctions appears to be sequestration of several GEFs for RhoA by AJ and TJ components.…”
Section: Mechanisms Activating Rac1mentioning
confidence: 99%